Pesantren 4.0: Integration of Steam in Classical Learning for Today’s Students - Mudayat Mudayat; Mualimin Mualimin; Ade Imelda Frimayanti; Eli Budi Santoso; Ichwan Ichwan (Universitas Muhammadiyah Enrekang, 2025)
The Industrial Revolution 4.0 has brought great changes in the world of education, including in the Islamic boarding school environment which has been relying on classical learning methods based on the yellow book. The gap in the use of information and communication technology (ICT) has caused pesantren to face challenges in preparing students to be able to compete in the digital era. The STEAM (Science, Technology, Engineering, Art, and Mathematics) approach is a solution that can be applied to improve the quality of learning in Islamic boarding schools without eliminating traditional values. This study uses a descriptive qualitative method with a case study approach at the Tri Bhakti Attaqwa Rama Puja Raman North Islamic Boarding School, East Lampung to explore the application of STEAM in the classical system. Data collection techniques were carried out through direct observation, in-depth interviews, and documentation studies, which were then analyzed by thematic analysis methods. The results show that the integration of STEAM in Islamic boarding school learning can improve 21st century skills, including critical thinking, creativity, and problem-solving. However, there are challenges in its implementation, such as the limitations of digital infrastructure, low technological literacy among students and teaching staff, and the need for special training for teachers in implementing STEAM. Therefore, an adaptation strategy is needed that maintains classical methods but still accommodates the use of technology in learning. This study provides recommendations for Islamic boarding schools to develop learning models that are more innovative and adaptive to the times